Method for synthesizing biphenyl compounds under composite catalytic actions of Pd/C and crown ether - SUN ZHIZHONG; YUAN XIAOBIN; CHU WENYI; LI HONGYU; LI XINMIN (2012)
The invention relates to a method for synthesizing biphenyl compounds under composite catalytic actions of Pd/C and crown ether, belonging to the field of synthesis of biphenyl compounds. The invention aims to solve the problems that the Pd/C catalyst used in the Pd/C catalyzed Suzuki coupling reaction can not be used cyclically, the cost for producing the biphenyl compounds is high, and the yield of the biphenyl compounds can not be higher than 95%. The method comprises the following steps: adding aryl halide and arylboric acid as reaction substrates in a mol ratio of 1:(0.8-4) into a reaction kettle; adding Pd/C and crown ether as a composite catalyst, adding potassium carbonate and adding methanol water solution; under inert gas shielding conditions, reacting at room temperature for 12-36 hours; and extracting, drying, filtering, carrying out vacuum concentration, carrying out chromatography, and eluting to obtain the biphenyl compounds. The invention is mainly used for synthesizing biphenyl compounds.